Digital Constitutionalism (Nomos Verlagsgesellschaft mbH & Co. KG, 2025)
Almost anything within constitutions, in particular the fundamental and human rights, are is in one or more aspects genuinely affected by the functionalities and effects of digitalization. Established legal understandings and hidden prerequisites on which constitutions are typically built are challenged. The authors analyse different methodological, substantial and comparative legal questions with a particular focus on Artificial Intelligence.